MINIMALLY INVASIVE INTERVENTIONS IN SURGICAL TREATMENT OF ACUTE BILIARY PANCREATITIS (World Bulletin of Public Health, 2025)
The paper presents a retrospective analysis of treatment of 221 patients with acute biliary pancreatitis. In case of stone embedding in the large duodenal papilla endoscopic papillotomy in the first hours is recommended, in case of choledocholithiasis, mechanical jaundice, cholangitis and acute biliary pancreatitis - endoscopic papillotomy and lithoextraction performed in the first day after the patient's admission to the clinic. Cholecystectomy, as a rule, laparoscopic, it is expedient to perform after conservative resolution of mild biliary pancreatitis in the next 3-7 days. After performing endoscopic papillotomy, it is justified to perform cholecystectomy also without discharge from the hospital, if the procedure is performed without complications. In acute biliary pancreatitis complicated by sterile or infected fluid accumulations, cholecystectomy should be postponed until their complete resolution and elimination of systemic inflammatory reaction
Keywords: Acute pancreatitis; surgical treatment; complications of acute pancreatitis